Effect of the sintering technique on the ferroelectric and d33 piezoelectric coefficients of Bi0.5(Na0.84K0.16)0.5TiO3 ceramic - Hernández Cuevas, Gamaliel (2019)
In the search of lead-free piezoelectric materials, ceramic processing techniques offer potential tools to increase the piezoelectric and ferroelectric properties in addition to new chemical compositions. Powders of pure BNKT16 (Bi0.5(Na0.84K0.16)0.5TiO3) phase were synthesized by sol-gel method with a low crystallization temperature (750 °C). Ceramic samples were sintered by pressureless sintering (PLS), sinter-forging (SF), and spark plasma sintering (SPS) techniques. Structural, morphological, and chemical characterizations were performed by XRD, Raman, EDS, and SEM. Sintered samples by PLS and SF exhibit rod-like grains associated to bismuth volatility. The highest remanent polarization (11.05 μC/cm2), coercive field (26.2 kV/mm), and piezoelectric coefficient (165 pC/N) were obtained for SF sample. The piezoresponse force microscopy (PFM) analysis shows that the crystallites at the nanoscale exhibit piezoelectric phenomenon and the highest piezoelectric response is reported for PLS sample. The presence of the rhombohedral phase, the increase in grain and crystallite size, and the oriented rod-like inclusions favoring the crystallographic texture are facts that enhance the piezoelectric coefficient for BNKT16 piezoceramics.